Preliminary ecological input assessment and EIA for coastal resort development in Malaysia - Vun, Leong Wan; A. Latiff (1999)
In Malaysia, en vironmen ta1 impact assessment (EIA) has been mandatory since 1988 in 19 prescribed activities. This study explores the quality of ecological input in EZA reports for coastal resort development in Peninsular Malaysia. The majority over-relied on descriptive and subjective methods, and gave details that are not site-spectfic or current. In describing the existing environment, there is a bias towards sampling easily surveyed groups such as terrestrial fauna and flora. Many failed to provide data adequate for predicting potential ecological impacts, and none attempted to quanttfy the impacts. Proposed mitigating measures often lack prescriptive detail. Possible residual impacts are only addressed in passing. Overall, reports were lacking considerably in ecological vigour.